Dysfunctional uterine bleeding (H.U.D.). Differential diagnosis. - Herrera Calmet, Abelardo (2015)
To avoid errors in the diagnosis of dysfunctional uterine bleeding, it should be a comprehensive examination; clinical and gynecological thorough and proper examination and laboratory findings rule oriented organic processes justify the uterus and ovarian dysfunction as the cause of endometrial bleeding. In our study, 27.8% of cases of unsuspected organ damage uterus was found, being the fibroid with 14.2%, the most common cause; He followed in order of frequency adenomyosis with 8.7%; endometrial polyp with 3.2% and in situ cervical cancer, with 1.1%.